PENGARUH PENERAPAN TEKNIK SPOTLIGHT DISERTAI HANDOUT TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN BATANG KAPAS KABUPATEN PESISIR SELATAN - Gusnita, Helmi; Aima, Zulfitri; Haryono, Yulia (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This research was grounded by the studentsâ low understanding on mathematics concepts, unwillingness to ask questions and express ideas, and lack of confidence in answering the questions given. One of the efforts done to solve these problems was by applying spotlight technique assisted with handout. This research was aimed at revealing whether the conceptual understanding of the students taught by using spotlight technique assisted with handoutÂ was better than that of students taught by using conventional learning in class VIII of MTsN Batang Kapas. This was an experimental research. The population of the research was the studentsÂ in class VIII of MTsN Batang Kapas. The instrument of the researchÂ was a test on mathematics conceptual understanding. The result of the hypothesis test showed that the value of tcalculated was bigger than ttable signifying that the conceptual understanding of the students taught by using spotlight technique assisted with handout was better than that of students taught by using conventional learning in class VIII of MTsN Batang Kapas. Â